2022
DOI: 10.1108/medar-12-2020-1120
|View full text |Cite
|
Sign up to set email alerts
|

The effect of innovation on environmental, social and governance (ESG) practices

Abstract: Purpose This paper aims to investigate if and to what extent environmental, social and governance (ESG) practices are influenced by innovation, measured by investment in research and development (R&D) and the number of patents developed by companies. Design/methodology/approach To test this hypothesis, the authors estimated a regression model for the panel data considering a time horizon of eight years. The analysis was conducted on a sample of listed firms operating in the industrial sector in France, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 66 publications
3
30
0
2
Order By: Relevance
“…The findings were not unexpected, given that the UK was the foremost to initiate governance reforms, based on the recommendations of the Committee on the Financial Aspects of Corporate Governance (1992), popularly known as the Cadbury report, while the United States and Australia saw big corporate fraud in 2000 (Singh et al, 2021). Recently, environmental regulation, ESG portfolios, innovation, socially responsible investment, and pension funds have been the subject of studies in the United States (Alda & Vicente, 2021; Dicuonzo et al, 2022; Mukherjee & Sohrabji, 2022; Ouchen, 2021). The United Kingdom has been concentrating on the ESG-liquidity-stock-return nexus, exchange-traded funds, innovation, socially responsible investment, and pension funds (Albitar et al, 2022; Dicuonzo et al, 2022; Rompotis, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings were not unexpected, given that the UK was the foremost to initiate governance reforms, based on the recommendations of the Committee on the Financial Aspects of Corporate Governance (1992), popularly known as the Cadbury report, while the United States and Australia saw big corporate fraud in 2000 (Singh et al, 2021). Recently, environmental regulation, ESG portfolios, innovation, socially responsible investment, and pension funds have been the subject of studies in the United States (Alda & Vicente, 2021; Dicuonzo et al, 2022; Mukherjee & Sohrabji, 2022; Ouchen, 2021). The United Kingdom has been concentrating on the ESG-liquidity-stock-return nexus, exchange-traded funds, innovation, socially responsible investment, and pension funds (Albitar et al, 2022; Dicuonzo et al, 2022; Rompotis, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Recently, environmental regulation, ESG portfolios, innovation, socially responsible investment, and pension funds have been the subject of studies in the United States (Alda & Vicente, 2021; Dicuonzo et al, 2022; Mukherjee & Sohrabji, 2022; Ouchen, 2021). The United Kingdom has been concentrating on the ESG-liquidity-stock-return nexus, exchange-traded funds, innovation, socially responsible investment, and pension funds (Albitar et al, 2022; Dicuonzo et al, 2022; Rompotis, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albort-Morant, Leal-Millán [126], Huang, Hu [127] and Tang, Qiu [128] described green innovation as having a positive impact on the management of internal dynamic dimensions, pressure from market and customers as well as compliance with environmental regulations. Dicuonzo, Donofrio [129] identified a positive relationship between ESG performance and innovation, measured by R&D investment and the number of patents developed by firms. As an innovation, De Santis and Presti [130] suggested that big data could help achieve sustainability.…”
Section: The Mediating Role Of Innovation On the Relationship Between...mentioning
confidence: 99%